Market instability and economic complexity: Theoretical lessons from transition experiments - Ping Chen (Transformation, Integration and Globalization Economic Research (TIGER), 2007)
The 'Washington consensus' and 'shock therapy' approach to transition economies ignored the Keynesian lessons from the Great Depression: that market instability is a possibility and there may be an active role of government in managing stability and growth. The severe output decline in East Europe and the former Soviet Union (EEFSU) was triggered by a simplistic policy of liberalisation and privatisation, which ignored many economic complexities and the existence of multiple equilibria under alternative divisions of labour. Issues of fundamental importance, such as the chain reaction between macroeconomic instability and microeconomic behavior, the role of the government in creating learning space in development, interactions between economic openness, sustainable growth, and social stability, can all be revealed from comparative experiments between China and EEFSU. These include the role and impact of exchange rate regimes, price dynamics, trade policies, and reform strategies. The tremendous cost of the Transition Depression sheds new light on theoretical limitations of atomic demand and supply analysis, theory of hard-budget constraints, microfoundations in macroeconomics, and the property rights school in institutional economics. New development policy based on learning, innovation, and decentralised experiments will pave the way for new thinking in complex economics.
Keywords: 330; Systemtransformation; Wirtschaftsreform; Wirtschaftliche Instabilität; Wirtschaftskrise; Wirtschaftliche Anpassung; Wirtschaftsliberalismus; Transformationsstaaten